Governance for Resilient Rural Livelihoods in the Face of Pandemics and Disasters – Insights from Rural South Africa - Betty Claire Mubangizi (E-Journal of Humanities, Arts and Social Sciences, 2025)
Rural livelihoods play a crucial role in South Africa’s socio-economic development but face significant challenges, such as poor infrastructure, environmental risks and economic marginalisation. Policies like the Comprehensive Rural Development Programme aim to address these issues, but gaps in policy formulation, weak implementation, and inadequate participation by the affected community often limit their impact. Effective governance that aligns national priorities with local needs is essential for achieving sustainable rural livelihoods. This study examined the relationship between policy implementation, governance, and rural engagement in the face of pandemics and disasters. Data were collected during eleven interviews and two focus group discussions in the Alfred Nzo District Municipality in South Africa. The findings highlight the importance of micro-level, place-based development, integrating community-driven initiatives with broader policy frameworks. The study established that robust localised planning, inclusive governance, and participatory decision-making build the resilience of rural communities and ensure that the development strategies implemented in these communities align with their reality. The study also emphasises the need for institutional mechanisms that strengthen the capacity and agency of local government actors to lead development initiatives. Given the growing challenges posed by climate change, disasters and pandemics, this paper made actionable recommendations to improve governance, expand the participation of rural communities in policymaking, and integrate disaster management strategies into local economic development. The use of the sustainable livelihoods framework in this research makes its findings relevant to the current discourse on how to shape policy and strategy to achieve equitable, community-centred, and adaptive rural governance in South Africa.